2008
DOI: 10.1044/cicsd_35_s_72
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prolonged Pacifier Use on Speech Articulation: A Preliminary Investigation

Abstract: This investigation was designed to study the impact of prolonged pacifier use on speech articulation. Three groups of children representing varying degrees of pacifier use ranging from little or none to 55 months were formed. Group 1 consisted of 30 children who had no or minimal history of pacifier use. Group 2 consisted of 16 children who had a history of pacifier use for up to 15 months. Group 3 consisted of 22 children who had a history of pacifier use that ranged from 18 to 55 months. Each child was admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 4 publications
0
16
1
1
Order By: Relevance
“…However, it is reasonable to hypothesize that such a relationship is likely to exist, 8,9,11,12,14,15 but a causal relationship has not been established and the issue remains controversial. 16 Besides, pacifier use has been related to atypical development of oral functions, 17 increased incidence of acute otitis media and other infections, [18][19][20] speech problems, 21 malocclusion, 22,23 lower levels of intelligence, 24 and more recently, the development of unhealthy lifestyles in adulthood including smoking, overeating, and other compulsive disorders. 25,26 Based on the assumption that pacifier use impairs the establishment and continuation of EBF, the WHO strongly discourages its usage.…”
Section: Np53mentioning
confidence: 99%
“…However, it is reasonable to hypothesize that such a relationship is likely to exist, 8,9,11,12,14,15 but a causal relationship has not been established and the issue remains controversial. 16 Besides, pacifier use has been related to atypical development of oral functions, 17 increased incidence of acute otitis media and other infections, [18][19][20] speech problems, 21 malocclusion, 22,23 lower levels of intelligence, 24 and more recently, the development of unhealthy lifestyles in adulthood including smoking, overeating, and other compulsive disorders. 25,26 Based on the assumption that pacifier use impairs the establishment and continuation of EBF, the WHO strongly discourages its usage.…”
Section: Np53mentioning
confidence: 99%
“…Articulation problems can arise from dental malocclusions, which can lead to distortion of fricatives and alveolar phonemes (Boshart 2001). Given that dummy use and speech production share similar oro-motor mechanisms and control, placement of the dummy in the oral cavity creates reduced opportunities for babbling and production practice, including of early words (Burr et al 2020, Shotts et al 2008. Babbling is an important precursor to the development of speech, allowing the child production practice, which equips them with the motor control necessary for refining and rescaling early vocalizations, supporting them in their journey towards more complex adult-like sound production (Green et al 1997, Nip et al 2011, Oller et al 1999, Steeve and Moore 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Children who had used a dummy were found to be at least 10% less accurate at articulating alveolar phonemes than age-matched controls; however, they still scored within the average range and there was no clear relationship identified between articulation and duration of dummy use. Another study conducted by Shotts et al (2008) into the effects of prolonged dummy (defined as beyond 18 months) use on articulation skills focused on 68 English-speaking children from Arkansas, aged 2.00-6.05 years. Using a standardized speech assessment, Shotts et al (2008) found that there was no significant difference between children who had minimal dummy use (less than 1 month), typical dummy use (up to 15 months) and prolonged dummy use (beyond 18 months).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…das medidas de controle e normatização do marketing, com o avanço da tecnologia, a cada dia têm-se novos formatos e modelos de mamadeiras e As alterações oclusais mais frequentemente encontradas entre crianças usuárias de bicos artificiais são: mordida aberta anterior e mordida cruzada posterior(CARVALHO, 1998;LEITE et al, 1999;WARREN et al, 2002; MACIEL e LEITE, 2005;PERES et al, 2007). a cavidade oral, limitando o balbucio, a imitação dos sons e a emissão das palavras, levando por vezes uma vocalização distorcida(NEIVA at el., 2003;SHOTTS et al, 2008;BARBOSA et al, 2009) et al, 1997a;AARTS et al, 1999;HOWARD et al, 1999;VOGEL et al,.…”
unclassified